Development of Moving Micro-Machines That Use Hydrogen Peroxide and Glucose as Fuels. (10th December 2015) - Kuzuoka, Takuya; Kouno, Tomohiro; Koyama, Tomohiro; Morita, Yuji; Yamazaki, Keitaro; Gunji, Takao; Tanabe, Toyokazu; Kaneko, Shingo; Nanzai, Ben; Matsumoto, Futoshi
Abstract : We developed micro-machines constructed using metal or polymer materials that move by converting the chemical energy of hydrogen peroxide (H2 O2 ) and glucose to the mechanical energy of dioxygen (O2 ) bubble impulses. The conversion process is based on electrochemical and enzymatic reactions. The micro-machines with enzymatic reactions exhibited a higher moving speed than the conventional micro-machines with electrochemical reactions. Our originally designed Au/Pt/cationic polymer/glucose oxidase (GOx)/catalase type micro-machines could move using glucose as fuel. However, the speed of movement achieved using glucose is much smaller compared with other micro-machines that move using H2 O2 as fuel.